Anti Metafisika Dalam Epsitemologi Immanuel Kant dan Kemungkinan Agama Sebagai Jalan - Muhammad Yunus (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2020)
The purpose of this study is to explore the underpinnings of Kant's doubts about metaphysics and its implications for epistemological problems. Some of the questions that will be answered in this study (1) What is the basis for Kant's doubts about metaphysical problems? (2) what are the implications of Kant's doubts on metaphysical questions? (3) How does religion provide answers to these answers? This research uses literature sources such as books, journals and relevant research reports. The analytical method uses hermeneutics which includes elements of description and interpretation. The result of this research is that Kant believes that every scientific decision comes from experience and reason. Meanwhile, nomena is a reality beyond the boundaries of knowledge. This view of Kant has implications for the search for new methods of approaching metaphysics. Religion is an alternative which needs to be considered as a method of understanding the nominal reality that Kant doubts. Religion has become a kind of epistemology for metaphysical problems.